Photoinduced Electron Transfer Modulated Photoelectric Signal: Toward an Organic Small Molecule-Based Photoelectrochemical Platform for Formaldehyde Detection - Gao, Yuan; Yu, Zhichao; Huang, Lingting; Zeng, Yongyi; Liu, Xiaolong; Tang, Dianping (Analytical chemistry (Washington), 2023)
Photoelectrochemical (PEC) sensing has been rapidly evolving in recent years, while the introduction of small molecules with specific recognition functions into the sensing interface remains a nascent area of study. In this work, we reported a PEC biosensor for formaldehyde (FA) detection based on photoinduced electron transfer (PET)-gated electron injection between organic small molecules and inorganic semiconducting substrates. Specifically, an FA-responsive probe (NA-FA-COOH) and TiO nanoarrays were integrated to construct a PEC platform (NFC/TiO ) via a coordination bond. NFC served simultaneously as a target-specific recognition element and a modulator of photoinduced electron injection. Treatment of NFC/TiO by FA would suppress the intramolecular PET process, with the quenched photocurrent signal due to the changed carrier transfer pathway, thus establishing the PEC platform for FA based on effective PET modulation. The proposed PEC system exhibited high selectivity and sensitivity, with a low detection limit of 0.071 μM. This study presents a novel perspective on the use of organic small molecules with a PET effect for advanced PEC bioanalysis.